A Case of Leukocytoclastic Vasculitis Caused by Listeria monocytogenes Bacteremia - Daniel R. Bunker; Timothy Sullivan (Case Reports in Infectious Diseases)
Importance. Infections can cause leukocytoclastic vasculitis. Observations. We report the case of a patient with a left ventricular assist device who presented with acute kidney injury and biopsy proven leukocytoclastic vasculitis. Blood cultures grew Listeria monocytogenes. The patient’s rash improved with treatment of the underlying Listeria infection. Conclusion. Clinicians should be aware that there are a number of broad categories of disease associated with the histologic finding of vasculitis, including infection. It is important to keep in mind the risk factors of a particular patient when formulating a differential diagnosis. This is the first reported case of Listeria bacteremia causing leukocytoclastic vasculitis.